Studi Kebijakan Pengambangan Titik Perekonomian Baru Provinsi Sumatera Selatan Melalui Pembangunan Pelabuhan Internasional Tanjung Carat - Mega Nugraha; Derriansya Putra Jaya (LPPM STISIP IMAM BONJOL, 2025)
The challenge for a regional head today is to create new economic points in each region that will provide hope and can create community welfare in the form of increasing employment opportunities, reducing unemployment rates, increasing community income above the Provincial Minimum Wage (UMP), and maintaining regional inflation rates. This study aims to identify the benefits and impacts that will be obtained from the construction of Tanjung Carat port in South Sumatra Province, including: 1) analyzing the increase in economic growth in South Sumatra province, 2) creating job opportunities, 3) reducing transportation logistics costs, 4) integrating the economic ecosystem of South Sumatra Province. The development of a new economic point in South Sumatra through the construction of the Tanjung Carat international port, the priority things that must be implemented by the local government include legal and regulatory certainty by providing easy and uncomplicated permits, protection of ownership rights for the land area to be built and consistency in implementing policies, fulfillment of basic infrastructure in the Sustainable Development Goals (SDGs), the employment aspect is the most important part in the implementation of the development and activities of the Tanjung Carat international port, the condition of a region, political and social stability, creating market access where proximity to the domestic or export market, providing investment incentives for business actors around the Tanjung Carat Port area